Tinjauan Yuridis Pasal 20 Undang-Undang Nomor 35 tahun 2014 tentang Perlindungan Anak terhadap Kesejahteraan Anak - Ryan Nugraha Yahya; Ayu Audrey Parahita N.; Bellia Argata Syahrani B.; Delvina Dhara Carissa (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
Child protection is an important need for the nation for the future. Children have human rights which must be respected and protected considering that they are at a vulnerable age. They have the right to grow and develop and be free from exploitation, violence or neglect. With good protection, you can ensure they are protected from dangers and can grow and develop in a good environment. The protection and welfare of children has become the responsibility of various instruments such as the family, community and state. Protection carried out by families and communities is implemented through a family approach based on moral values, while child protection by the state is carried out through policies or regulations that regulate this. The technique of research that was utilized in this study was a qualitative method, which involved conducting in-depth interviews to acquire this information. The data collected is comprehensive data, using both primary and secondary sources of information, which will be subjected to a methodical analysis in order to arrive at a conclusion based on the findings of the whole research.